2009
DOI: 10.1159/000237743
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Preterm Labor and Thrombophilic Gene Polymorphism: A Prospective Sequential Cohort Study

Abstract: Objective: Premature labor is still the leading cause of infant mortality and morbidity worldwide. Multiple etiological factors including genetics and environment are held responsible for preterm birth. However, scientific data regarding the link between premature birth and genetics are limited. Subjects and Methods: In this study, we included 50 women who had premature labor (group 1) but did not have any known risks for a premature delivery such as uterine anomaly, polyhydramnios, hypertension, and diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Good nutrition can reduce elevated hyperhomocysteinemia caused by mutations in the MTHFR gene. MTHFR-C677T and MTHF-A1298C showed only a minimal association with preterm delivery in both whites and blacks (Engel et al, 2006;Gargano et al, 2009) as well as in cases in Turkey (Uvuz et al, 2009) in some studies. Gargano also studied 560 whites and 399 blacks and showed that MTHFR-C677T and MTHFR-A1298C were only correlated with the placental-type premature birth, but had no correlation with the other types of premature births.…”
Section: Discussionmentioning
confidence: 95%
“…Good nutrition can reduce elevated hyperhomocysteinemia caused by mutations in the MTHFR gene. MTHFR-C677T and MTHF-A1298C showed only a minimal association with preterm delivery in both whites and blacks (Engel et al, 2006;Gargano et al, 2009) as well as in cases in Turkey (Uvuz et al, 2009) in some studies. Gargano also studied 560 whites and 399 blacks and showed that MTHFR-C677T and MTHFR-A1298C were only correlated with the placental-type premature birth, but had no correlation with the other types of premature births.…”
Section: Discussionmentioning
confidence: 95%
“…Recent genetic research has focused on infectious, thrombophilic, and renin‐angiotensin system pathways (Gargano et al, 2009; Kramer et al, 2009; Uvuz et al, 2009; Warren et al, 2009); however, no associations were found for thrombophilic gene polymorphisms and preterm labor (Kramer et al, 2009; Uvuz et al, 2009). Thrombophilic and renin‐angiotensin gene polymorphisms were associated with hemorrhage‐related preterm delivery, but not other types of preterm delivery (Gargano et al, 2009).…”
mentioning
confidence: 99%
“…Carriage of FII G20210A, which is rare in Finland, was not associated with preterm birth in our study. In the few other studies, the results have been controversial [8–12]. With our study population, the lowest OR for FII G20210A that would have been possible to detect with 80% power is 3.4.…”
Section: Discussionmentioning
confidence: 64%
“…No association between FV Leiden and preterm birth has been found in various studies [8–12]. Härtel et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation